Reflective Practice and Interactive Teaching - Montgomery, Philip (My University, 2015)
This presentation highlights the ways in which reflective practice, both by students and faculty can improve learning and achievement. The presentation gives examples of interactive teaching methods that lead to this improved reflection
Keywords: Reflective practice; higher education; interactive teaching methods